DISTRIBUTION AND SUSCEPTIBILITY PATTERN OF URINARY TRACT BACTERIAL PATHOGENS IN AN OUTPATIENT SETTING. A LABORATORY BASED STUDY–FAISALABAD - Sadia Hameed; Tariq Afzal (Journal of University Medical & Dental College, 1970)
ABSTRACT A retrospective study was conducted in the setting of a diagnostic laboratory (Meezan Lab) catering to tertiary care hospitals and out patient population of Faisalabad district. A total of 93 urine samples collected during a time period of 6 months from July 2011 to December 2011 and fulfilling the inclusion criteria were included in the study. The objective was to assess the distribution of urinary tract bacterial pathogens with respect to age and gender and to determine the antibiotic susceptibility profile of the isolates in our setting. Single positive cultures with a colony count of >105 CFU on CLED medium were identified and their antibiotic sensitivity and resistance profile was depicted in the form of an antibiogram. 78.4% of the total isolates were identified as E. coli, followed by Enterobacter spp. 6.45%, Staphylococcus aureus 6.45%, Pseudomonas aeruginosa 5.37%, Enterococcus fecalis 2.15% and Klebsiella pneumonia 1.07%. It was observed that 95.12% of total tested isolates were sensitive to Cefoperazone/sulbactam followed by Piperacillin/Tazobactam 94.4 %, Amikacin 90.5%, Cefipime 63.73%, Imipenem 62.65%, Gentamicin 52.5%, Ceftazidime 52.4%, Levofloxacin 45%, Sparfloxacin 37.5%, Ceftriaxone 34.6%, Enoxacin 26.6%, Ciprofloxacin 16.6%, Cotrimoxazole 13.95%. This is an alarmingly low sensitivity to Ciprofloxacin and Cotrimoxazole both of which are routinely used as empirical therapy for uncomplicated community acquired urinary tract infections and reinforces the need for proper sensitivity testing to guide the management of UTIs.